Rhetorical Refusals : Defying Audiences' Expectations - Schilb, John, 1952- (Book collections on Project MUSE., 2007)
The first book to explore rhetorical refusals- instances in which speakers and writers deliberately flout the conventions of rhetoric and defy their audiences' expectations- Rhetorical Refusals: Defying Audiences' Expectations challenges the reader to view these acts of academic rebellion as worthy of deeper analysis than they are commonly accorded, as rhetorical refusals can simultaneously reveal unspoken assumptions behind the very conventions they challenge, while also presenting new rhetorical strategies. Thr.